Evaluation of the Visit Program: Final Report - Hart, Kerry; Cassidy, Jack; Marett, Georgia; Rutherford, Jack; Siriwardena, Pravin; Hodge, Wendy; Christian, Fiona (My University, 2021)
Open Support engaged ARTD Consultants to evaluate the Visit Program to assess the appropriateness of the service model, the benefits of the program to clients, and its cost-efficiency. The evaluation used a mixed-methods design, synthesising qualitative data collected from program staff, volunteer coordinators, visitors, and clients, with quantitative data from client surveys, HILDA Wave 18 Survey data and program activity and costs data. The evaluation sought to answer questions about whether or not the program reduces the negative effects of social isolation and if any components of the service model should be changed and the client group expanded. The evaluation found that Visit Program is highly valued by partner agencies, program staff and clients because it fills a service need not met by other providers where it is offered. Clients feel less socially isolated and look forward to the visits from their visitor, enjoy the activities they do with them, and appreciate having someone to talk to confidentially, who is non-judgmental and can offer advice or a new perspective. Overall, the economic evaluation showed that the Visit Program is a sound investment for the community. A cost-benefit analysis showed that Visit Program is delivering economic value to the community with a benefit-cost ratio of roughly 2:1 and a net benefit of over $500,000 largely due to the program’s impact on its clients’ quality of life.
Keywords: Disadvantage, adversity and resilience; Health and wellbeing; Social engagement